Skladnost postopkov za odvzem nadzornih kužnin za ugotavljanje kolonizacije bolnikov s proti meticilinu odpornim Staphylococcus aureus z uveljavljenimi smernicami dela - Zaremba, Ostap (Rehabilitacija (Ljubljana), 2015)
Background Colonised patients with methicillin-resistant Staphylococcus aureus (MRSA) are discovered with screening program. Patients colonized with MRSA need measures of contact isolation to prevent propagation of MRSA to other patients and healthcare workers. With this study we wanted to determine, according to the guidelines adopted, weather the screening for MRSA carriers among patients that were admitted to rehabilitation program in a specific time period is performed adequately. Methods We retrospectively compared the data from the medical records of patients aged over 18 years who have been admitted to the rehabilitation program over a period of one month with the indications defined in the adopted guidelines for MRSA screening in the Programme for the prevention of nosocomial infections at URI - Soča. We determined which patients were screened for MRSA on the basis of indications, which patients were not screened despite indications and which patients were screened without indications. Results In the period under investigation it was taken 89 adult patients to the rehabilitation program at URI - Soča, of whom 51 (57%) men and 38 (43%) women, average age of patients was 56.1 years. In relation to adopted indications the screening for MRSA colonised patients on admission was required in 29 cases, actually screening was made in 8 cases. In 21 cases, despite the indications, the screening was not done, in 7 cases the screening was done without indications. Conclusion According to the guidelines adopted, the number of screening for MRSA colonised patients at URI - Soča is insufficient.
Keywords: colonization; kolonizacija; Methicillin-Resistant Staphylococcus aureus; MRSA; nadzorne kužnine; rehabilitacija; Rehabilitation; screening; vocational rehabilitation